A extrafiscalidade tributária como instrumento fomentador do princípio do protetor recebedor - Moraes, William Thiago de (2019)
The defense and preservation of the environment are state duties and the fundamental right of all individuals, including assured to the future generations. With regard to the normative principle of constitutional order that imposes the state of a power-duty, it is imperative that they are viable, from mechanisms of environmental protection, to reach the end. The objective of this work is to analyze the feasibility of the use of the national tax system as an instrument to reach the constitutional precept of environmental research, with the addition of a differentiated tax treatment for environmentally protected driving, with the application of taxation in its extra-fiscal purpose. An integration of the legislation and precepts of Environmental and Tax Law was sought, in the form of a preview of the Premial Law, supported by the protector of the principle-receiver and an extra-fiscal environment. The methodology adopted for the research and dissemination of thematic data in the bibliographic research, but also uses primary sources and documentary research for the collection and qualitative analysis of the data. As the verification of environmental, tax and environmental performance, including the increase of environmental extrafiscality in federal, state and municipal laws, with the implementation of tax mechanisms that apply the tax legislation, which directly or indirectly benefit the environment. It is also evident that the legal system presents constitutional permissive for the institution of a new principle by the Union, no exercise of its residual competence, which could have a markedly extraphysical character, of an environmental nature, given the freedom to constitute constitutional, normative for this institution. Lastly, there is a legislative gap that applies to the application of environmental tax extrafiscality, which is not a taxation of the carbon market.